2016
DOI: 10.1111/lang.12166
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Systematicity and Individuality in Nonlinear Second Language Development: The Case of English Grammatical Morphemes

Abstract: This article introduces two sophisticated statistical modeling techniques that allow researchers to analyze systematicity, individual variation, and nonlinearity in second language (L2) development. Generalized linear mixed-effects models can be used to quantify individual variation and examine systematic effects simultaneously, and generalized additive mixed models allow for the examination of systematicity, individuality, and nonlinearity within a single model. Based on a longitudinal learner corpus, this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
51
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 61 publications
4
51
0
1
Order By: Relevance
“…Mixed‐effects models present various advantages compared to means‐based parametric statistical techniques such as ANOVAs and t tests (Cunnings, ; Cunnings & Finlayson, ; Gries, ; Linck & Cunnings, ; Murakami, ). For example, as Cunnings () noted, the fixed effects component in a model can comfortably accommodate multiple independent variables, including categorical variables (males vs. females, L1 vs. L2), continuous predictors (age), as well as a mixture of both.…”
Section: Background Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Mixed‐effects models present various advantages compared to means‐based parametric statistical techniques such as ANOVAs and t tests (Cunnings, ; Cunnings & Finlayson, ; Gries, ; Linck & Cunnings, ; Murakami, ). For example, as Cunnings () noted, the fixed effects component in a model can comfortably accommodate multiple independent variables, including categorical variables (males vs. females, L1 vs. L2), continuous predictors (age), as well as a mixture of both.…”
Section: Background Literaturementioning
confidence: 99%
“…Ironically, Gries () dubbed mixed‐effects models “the most under‐used statistical method in corpus linguistics” (p. 95), and, by extension, in learner corpus research. Only a handful of published studies have employed mixed‐effects modeling for (various) longitudinal learner corpus data (Crossley, Skalicky, Kyle, & Monteiro, ; Crosthwaite & Jiang, ; Meunier & Littré, ; Murakami, ) and only one study to date has used mixed‐effects models to explore L2 phraseological development over a period of time (Spina, , see above). Echoing Cunnings (), Gries () noted that corpus linguistics can benefit from mixed‐effects models for the reasons similar to those for which psycholinguists have been using them for over a decade.…”
Section: Background Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A MAJOR FOCUS OF SECOND LANGUAGE acquisition (SLA) research to date has sought to understand the competition and relationships between a learner's different languages (Calabria et al., ). This research has repeatedly shown that the use of a single language activates a speaker's other known languages (Marian & Spivey, ; Wu & Thierry, ), that prior first language (L1) knowledge and experience can influence second language (L2) use (e.g., selective attention to linguistic cues; Ellis & Sagarra, ; MacWhinney, ), and that L1–L2 differences can influence the route and rate of L2 morphosyntactic development and processing (Avery & Marsden, 2019; Isabelli, ; McManus, , ; Murakami, ; Roberts & Liszka, ). However, despite major advances in what we know about the cognitive effects and mechanisms of learning a second language, little research has systematically examined the next step in this program: How can this understanding about the competition and relationships among a learner's different languages be used to facilitate L2 learning and teaching?…”
mentioning
confidence: 99%
“…Because mixed-effects models have been described extensively elsewhere (Cunnings & Finlayson, 2015;Curran, Obeidat, & Lisardo, 2010;Linck & Cunnings, 2015;Murakami, 2016;Singer & Willet, 2003), only a brief overview is presented here. Growth curve models are a subclass of mixed-effects models that estimate between-and within-individual change over time through fixed and random effects.…”
Section: Summary Of Growth Curve Modelingmentioning
confidence: 99%